Assessment of the Optic Nerve Head Parameters Using Heidelberg Retinal Tomography III in Preterm Children - Salem, Alshaarawi; Ismail, Shatriah; Embong, Zunaina; Wan Hitam, Wan Hazabbah (Public Library of Science (PLoS), 2014)
Background: Variations in optic nerve head morphology and abnormal retinal vascular pattern have been described in preterm children using digital image analysis of fundus photograph, optical coherence tomograph and serial funduscopy. We aimed to compare the optic nerve head parameters in preterm and term Malay children using Heidelberg Retinal Tomograph III. Design: A cross sectional study. Methodology/Principal Findings: Thirty-two preterm Malay children who were born at up to 32 weeks postconception, and 32 term Malay children aged 8–16 years old were recruited into this cross sectional study, which was conducted in the Hospital Universiti Sains Malaysia, Malaysia from January to December 2011. Their optic nerves were scanned and analyzed using a Heidelberg Retinal Tomography (HRT) III (Heidelberg Engineering, Germany). Preterm children showed an increased rim volume (SD) (0.56 (0.26) vs 0.44 (0.18) mm3, respectively), smaller cup shape (SD) (0.18 (0.07) vs 0.25 (0.06) mm, respectively), increased height variation contour (SD) (0.44 (0.14) vs 0.35 (0.08) mm, respectively), and increased cup depth (SD) (0.24 (0.11) vs 0.17 (0.05) mm3, respectively) when compared to their normal peers (p,0.05). There were no significant differences in the mean disc area, cup area, cup to disc ratio or rim area between the preterm and term children (p.0.05) in our study. Conclusions/Significance: Preterm children exhibit different characteristics of optic nerve head parameters with HRT III analysis. Increased cup depth in preterm children suggests a need for close observation and monitoring. It may raise suspicion of pediatric glaucoma when proper documentation of intraocular pressure and clinical funduscopy are unsuccessful in uncooperative children.